2019
DOI: 10.1249/mss.0000000000002216
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness, Physical Activity, and Insulin Resistance in Children

Abstract: Few studies have investigated the independent and joint associations of cardiorespiratory fitness (CRF) and body fat percentage (BF%) with insulin resistance in children. We investigated the independent and combined associations of CRF and BF% with fasting glycaemia and insulin resistance and their interactions with physical activity (PA) and sedentary time among 452 children aged 6-8 years. Methods: We assessed CRF with a maximal cycle ergometer exercise test and used allometrically scaled maximal power outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 53 publications
5
13
0
Order By: Relevance
“…In the present study, the non-MetS group was the only group that met this recommendation. Previous studies have reported the possible mechanisms by which high cardiorespiratory fitness prevents and reduces the prevalence of MetS; low cardiorespiratory fitness may lead to decreased arterial compliance and worse insulin resistance and may cause hyperglycemia and reduced physical activity [16][17][18]. Based on the recommendations, results of previous studies, and the findings of this study, it seems that high For many years, muscle strength has been widely accepted as an independent predictor of MetS [19].…”
Section: Discussionmentioning
confidence: 63%
“…In the present study, the non-MetS group was the only group that met this recommendation. Previous studies have reported the possible mechanisms by which high cardiorespiratory fitness prevents and reduces the prevalence of MetS; low cardiorespiratory fitness may lead to decreased arterial compliance and worse insulin resistance and may cause hyperglycemia and reduced physical activity [16][17][18]. Based on the recommendations, results of previous studies, and the findings of this study, it seems that high For many years, muscle strength has been widely accepted as an independent predictor of MetS [19].…”
Section: Discussionmentioning
confidence: 63%
“…Finally, the following 103 articles were selected: [ 24 34 , 44 135 ] after the evaluation of the full texts, 78 were excluded for the following reasons: (1) the design of the studies did not meet the inclusion criteria defined for this review [ 44 46 , 48 53 , 55 57 , 59 61 , 65 , 66 , 68 73 , 79 , 81 , 84 , 86 , 88 91 , 97 , 100 104 , 106 , 108 , 110 , 112 117 , 119 – 122 , 124 132 , 134 , 135 ] (2) the studies did not present an evaluation of whole body FFM/LBM, these were [ 47 , 54 , 58 , 62 64 , 67 , 74 78 , 80 , 82 , 83 , 85 , 92 96 , 105 , 107 , 109 , 111 , 123 ] and (3) another language [ 87 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Physical fitness is also strongly associated with metabolic health in adolescents. Specifically, higher fit adolescents have a lower degree of fasting insulin resistance, compared to their low-fit counterparts (Dring et al, 2019b;Haapala et al, 2020). Despite this, it is unknown if the physical fitness of participants moderates the acute metabolic responses to exercise and whether there are any overall associations of fitness with postprandial insulinaemia and glycaemia.…”
Section: Introductionmentioning
confidence: 99%